Evaluasi Program Kota Tanpa Kumuh (KOTAKU) di Kelurahan Sri Meranti Kecamatan Rumbai - Utary Ayu Tamara; Harapan Tua Ricky Freddy Simanjuntak (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This research aims to provide an overview of the evaluation of the City Without Slums (KOTAKU) program in Sri Meranti Village, Rumbai District, Pekanbaru City. The theory used in this research is Evaluation Theory according to William N Dunn (2003) which consists of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy. The research used qualitative research methods, with data collection through observation, documentation and interviews with the Head of KOTAKU Facilitator, Head of LKM, Head of PPM, and the community of Sri Meranti Village. The results of the research show that from the six theoretical contexts of the KOTAKU program evaluation, it has been proven that it has not run optimally in improving the quality of life of the community through improving infrastructure and basic services. There are still obstacles factors found in this program, namely changes in the person in charge of the program, limited human resources (HR), coordination. weak, limited infrastructure and resources, low community participation. In conclusion, the KOTAKU program is an excellent program for improving the quality of the community's living environment, but it is necessary to pay attention to the importance of coordination between related parties, training for human resources as implementers of the KOTAKU program, and increasing community participation related to this program.